Analisis Swot Dalam Penentuan Strategi Implementasi Pedagang Bozz Juice Ice Cream Dalam Menghadapi Persaingan - Utari Amalia Putri; Viona Ramifa Reja; Rani Pertama Sari; Ramdani Bayu Putra (Jurnal Bintang Manajemen, 2023)
Business strategy is an important part that must be owned by every business actor. This study tries to determine the ideal strategy through SWOT analysis. The object of this research is Cafe 165 which is a business unit of Putra Indonesia University YPTK Padang. The research method used is descriptive method with data collection techniques through interviews and questionnaires to the parties or stakeholders. SWOT Analysis techniques include IFE, EFE, CPM, TOWS, IE, SPACE, Grand Strategy and QSPM. The findings of the IFE Matrix and the matrix show that Bozz Juice Ice Cream has strong organizational characteristics internally with strategies that can take advantage of strengths that minimize weaknesses and are able to take advantage of opportunities from threats encountered. The results of the analysis of the TOWS Matrix, SPACE, IE, Grand Strategy as the final result of this study recommend that the right business strategy for Bozz Juice Ice Cream is implementing a market development strategy followed by product development through continuous innovation.